PENGARUH TERAPI TEMBANG BALI TERHADAP INSOMNIA DAN PENURUNAN TEKANAN DARAH PADA LANSIA YANG MENDERITA HIPERTENSI DI DESA KEROBOKAN KELOD KECAMATAN KUTA UTARA KABUPATEN BADUNG - Putu Wira Kusuma Putra (Indonesian Journal of Health Development, 2019)
Elderly age generate different kinds of degenerative diseases which affect health as well as the impact of sleep disorders and increased blood pressure. One way to alleviate insomnia and blood pressure in the elderly age is ‘listening to music’ (Balinese Therapy Song). The purpose of this study was to determine The Therapeutic Effect of Balinese Song against Insomnia and Controlled Blood Pressure to Elderly with Hypertension in Kerobokan Kelod Village Kuta Utara District of Badung. This research is a quantitative research with Quasi-Experimental Design method and Nonequivalent With Control Group Design. The sampling technique used in the research is Purvosive Sampling. The number of samples are 30 people, divided into 15 treatment groups and 15 control groups. Data analysis using statistic Mann-Whitney Test to compare the posttest between the treatment and control groups.The research results with Mann-Whitney Test showed that significant value p value 0,001 <α (0,05), concluded that there is a difference in the degree of insomnia between the group that are treatened with Balinese Therapy Song and that are not. As well as the results that showed on their blood pressure, Mann-Whitney Test obtained systolic blood pressure 0,001 <α (0,05), diastolic blood pressure, 0,002 <α (0,05), concluded that there is a difference in systolic and diastolic blood pressure in the treatment and control group. This research is expected to used as a non-pharmacological therapy in treating elderly with insomnia and hypertension and also used as additional literature in the future research